Perkalian Matematika Cepat Batch 2 pada Kelas X di MA Darussalam Manuju Kabupaten Gowa - Nur Aisyah; Azwan Anwar; Rahmah Musda Muin (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
This service aims to explain the increase in mathematics learning outcomes in multiplication material by applying the fast mathematical multiplication method in class XII at MA Darussalam Manuju. Data collection techniques use observation, interviews and documentation techniques. The method used was classroom action research, the research subjects were teachers and 15 class XII students. Instruments include interview sheets, observation sheets and learning results test sheets. using the Kemmis and Mc Taggart research design model. The results show that the application of the fast mathematical multiplication method can improve students' mathematics learning outcomes and understanding of multiplication. This can be proven based on the percentage results of cycle I and cycle II. The percentage of 0% in the very good category in cycle I increased to 60% in cycle II.